2021
DOI: 10.1038/s41567-021-01404-y
|View full text |Cite|
|
Sign up to set email alerts
|

Charge order and superconductivity in kagome materials

Abstract: Lattice geometry, topological electron behaviour and the competition between different possible ground states all play a role in determining the properties of materials with a kagome lattice structure. In particular, the compounds KV3Sb5, CsV3Sb5 and RbV3Sb5 all feature a kagome net of vanadium atoms. These materials have recently been shown to exhibit superconductivity at low temperature and an unusual charge order at high temperature, revealing a connection to the underlying topological nature of the band st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
147
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(150 citation statements)
references
References 51 publications
2
147
0
1
Order By: Relevance
“…Recent quantum oscillation [46] and ARPES [11,12] studies suggested that vanadium bands around the M point become gapped, in line with theoretical proposals of band saddle points at M as the main origin of the density-wave instability [15,48]. The presence of multiple d-bands in AV 3 Sb 5 [7] implies that this instability can have more than one energy scale revealed by several gap features that were indeed detected spectroscopically, but only with surface-sensitive techniques, so far [11,12,20].…”
Section: Energy Scale Of the Charge-density Wavesupporting
confidence: 53%
See 1 more Smart Citation
“…Recent quantum oscillation [46] and ARPES [11,12] studies suggested that vanadium bands around the M point become gapped, in line with theoretical proposals of band saddle points at M as the main origin of the density-wave instability [15,48]. The presence of multiple d-bands in AV 3 Sb 5 [7] implies that this instability can have more than one energy scale revealed by several gap features that were indeed detected spectroscopically, but only with surface-sensitive techniques, so far [11,12,20].…”
Section: Energy Scale Of the Charge-density Wavesupporting
confidence: 53%
“…This results in an overall quasi-2D structure with well-isolated kagome planes. All key features of a nearest-neighbor kagome metal -linear bands, saddle points, and flat bands -can be indeed distinguished in electronic structures of AV 3 Sb 5 [7].…”
Section: Introductionmentioning
confidence: 94%
“…Due to their inherent geometric frustration and unique band structure, kagome materials [1] represent an excellent platform for discovering, classifying and under-standing correlated electronic phases of quantum matter [2][3][4][5][6]. The novel family of kagome metals AV 3 Sb 5 (A = K, Rb, Cs) [7][8][9][10][11] exhibit an array of interesting effects such as giant anomalous Hall conductivity [12,13], charge order [11,[14][15][16][17][18][19][20][21][22], orbital order [23], and possible unconventional superconductivity [7,8,10]. An important feature of the charge order, which onsets at temperatures T co ∼ 100 K at ambient pressure, is the breaking of time-reversal symmetry, as reported by scanning tunneling microscopy (STM) measurements [11,14,15,17] in (K,Rb,Cs)V 3 Sb 5 , by muon spin relaxation (µSR) in KV 3 Sb 5 [24] and CsV 3 Sb 5 [25], and by Kerr effect measurements in CsV 3 Sb 5 [26].…”
mentioning
confidence: 99%
“…Several different CDW orders have been observed and/or suggested, including the one with broken time-reversal symmetry 2-13, [26][27][28][29][30][31][32][33] . Whereas some important experimental features remain controversial [9][10][11][21][22][23][24][34][35][36] , theoretical studies have been actively conducted in order to provide a plausible understanding of their microscopic origins and the interrelationships between different orders, stimulating further explorations [11][12][13][15][16][17][18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%